Modeling and Simulation Techniques for ITS Designs - Ghosh, Sumit; Lee, Tony S. (Intelligent Transportation Systems, 2010)
A key characteristic of intelligent transportation system (ITS) designs, as explained in Chapter 3 and reﬂected in Chapters 4 through 7, is that each entity, for example locomotives, cars, and so on, carries its own computing engine while subject to transportation through the system, under asynchronous, distributed algorithm control. Every entity is viewed as an asynchronous and autonomous process with welldeﬁned computational and communications needs. While some processes may be “stationary,” others are “mobile” within the transportation system. The exact pattern of migration of the mobile processes is dictated by the nature of the transportation system and the actual input data. The migration pattern is further complicated by the fact that every mobile process is autonomous, that is, every mobile entity determines its own migration pattern based on its unique behavior, input stimulus, and dynamic interactions with the stationary entities. Every mobile and stationary entity is characterized by unique computation and communication needs. Furthermore, the nature of the migration is asynchronous, that is, it is initiated at irregular intervals of time and may not be known a priori. Finally, in many transportation systems, the number of mobile and stationary entities is likely to be large, which, in turn, necessitates a distributed, scalable approach to modeling and simulation.